Modelling innovation as toxic (techno-economic) positivity: Some consequences of SPRU’s attack on “The Limits to Growth” - MacNeil, Ryan (NOvation — Critical Studies of Innovation, 2025)
The Science Policy Research Unit (SPRU) at the University of Sussex played a significant role in establishing innovation studies as a field and in establishing innovation policy as a framework for governmental thinking. But the SPRU’s first book was not directly about innovation; it was “Thinking about the future: a critique of the Limits to Growth” (1973). The “Limits to Growth” (1972) had been an attempt by researchers at MIT, funded by the Club of Rome and the Volkswagen Foundation, to quantitatively falsify the idea of endless growth on a finite planet. The SPRU’s response—later reprinted with the title “Models of Doom” outside the UK—was one of many that framed “Limits” as overly pessimistic. This paper considers the impact of this work on the developing fields of innovation research and policy. It takes a critical ethnostatistics approach to the modelling practices deployed by these two very different groups of professional social scientists. It focuses on two methodological moves made by the SPRU researchers. First, this paper shows how the SPRU arguments established a fetish for data precision—a standard that the MIT team rejected, but one that carried on through the SPRU’s further work into innovation research and policy. Next, it discusses how the SPRU researchers (role)modelled mathematical faith in socio-technical change. This was more than a techno-optimist (or Promethean) stance. It established a norm of toxic positivity around questions of technology, innovation, and the environment. These two methodological moves—fetishizing data precision while asserting toxically positive Prometheanism—became cultural memes that carried forward from this debate into innovation policy, modelling, and statistical practices. In short, the pro-innovation econometrics developed for this debate by the SPRU researchers had a lasting impact on the epistemic culture of innovation studies.